Structural Hippocampal Damage Following Anti-N-Methyl-D-Aspartate Receptor Encephalitis - Finke, Carsten; Kopp, Ute A.; Pajkert, Anna; Behrens, Janina R.; Leypoldt, Frank; Wuerfel, Jens T.; Ploner, Christoph J.; Prüss, Harald; Paul, Friedemann (Biological psychiatry (1969), 2016)
The majority of patients with anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis suffer from persistent memory impairment despite unremarkable routine clinical magnetic resonance imaging. With improved acute care in these patients, neurocognitive impairment represents the major contributor to long-term morbidity and has thus become a focus of attention. Forty patients with anti-NMDAR encephalitis after the acute disease stage and 25 healthy control subjects underwent multimodal structural imaging that combined volumetry of hippocampal subfields with analysis of hippocampal microstructural integrity. Verbal and visuospatial memory performance was assessed in all patients and correlation and mediation analyses were performed to examine associations between hippocampal structural integrity, memory performance, and disease severity. Hippocampal volumes were significantly reduced in patients and hippocampal subfield analysis revealed bilateral atrophy of the input and output regions of the hippocampal circuit. Microstructural integrity was impaired in both hippocampi in patients. Importantly, hippocampal volumetric and microstructural integrity measures correlated with memory performance and disease severity and duration. Mediation analysis revealed that hippocampal microstructure mediated the effect of disease severity on memory performance. Data from this largest cohort of anti-NMDAR encephalitis patients that underwent extensive multimodal magnetic resonance imaging demonstrate that structural hippocampal damage and associated memory deficits are important long-term sequelae of the encephalitis. Correlation with disease duration and severity highlights the need for rapid diagnosis and adequate immunotherapy to prevent persistent damage to the hippocampus. Advanced imaging protocols may allow a more detailed analysis of structural damage to assess disease progression in clinical routine examinations and for therapy evaluation in prospective trials.